Promoting the development of autonomy in the context of teletandem in language teacher education - ALVARADO , Martha Guadalupe Hernández; AVILÉS , Hilda Hidalgo; BUTRÓN , Norma Angélica Espinosa (The ESPecialist, 2022)
This paper reports findings from a study carried out in 2018 on the implementation of teletandem in a Bachelor of Arts in English Language Teaching (ELT) program in Mexico, as part of a learning autonomy course. The goals of the semi-structured teletandem exchange were to provide learners with the opportunity to 1) gain cultural and linguistic learning as a result of the interaction with native speakers and 2) develop and exercise their autonomy to learn English. Although all students enrolled in the course participated in the exchange, only 8 of them were selected to investigate the extent teletandem helped them develop and exercise their autonomy. Data come from the analysis of interviews with students. Findings revealed that the implementation of teletandem in the course made participants more aware of their autonomy and provided opportunities to exercise it. However, areas of improvement were identified to enhance the development of autonomy in teletandem. This study may be of interest to language teacher educators who seek to promote the development of autonomy in other learning scenarios apart from the language classroom. It could also be useful for language instructors and staff at language centers who are willing to improve the practice of telecollaboration in their own contexts.